Effects of protein supplementation strategy and genotype on milk composition and selected milk processability parameters in late-lactation spring-calving grazing dairy cows. (August 2021) - Doran, M.J.; O'Sullivan, M.; Mulligan, F.J.; Lynch, M.B.; Fahey, A.G.; McKay, Z.C.; Ryan, H.; Pierce, K.M.
Abstract: The objectives of this experiment were to investigate (i) if decreasing the supplement crude protein (CP) concentration whilst having equal protein digestible in the small intestine (PDI) would have an effect on milk composition and milk processability and (ii) if cow genotype interacted with protein supplementation strategy (PSS) on parameters measured. A 2 × 2 factorial arrangement experiment was conducted when cows were 198 ± 21.6 d in milking. Cows grazed full time and were offered 15 kg DM pasture cow −1 d −1 . There was no PSS × genotype interaction observed for any milk production, composition or processability parameter. Milk yield, protein kg, casein kg, fat + protein kg and milk urea nitrogen (MUN) decreased in cows fed 13% CP compared with those fed 18% CP. Decreasing supplementary CP concentration may have environmental benefits through decreased MUN which could indicate a reduction in urinary nitrogen excretion, while maintaining milk composition and processability parameters in pasture-based systems.